Prescription pattern analysis of antibiotic use in a paediatric intensive care unit of a tertiary care teaching hospital in South India - S., Sindhu; Ahmed, Syed Mohsin (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antibiotic resistance is rising to alarming levels that necessitates the evaluation of prescription patterns for the rational use of antibiotics. Hence this study was conducted to evaluate antibiotic use in a government run general hospital. Methods: A prospective observational study was conducted to evaluate the rationality of antimicrobial prescription in a paediatric intensive care unit (PICU) of a government run tertiary care teaching hospital using the USAID indicators for rational use of antibiotics. Case records of 104 patients were documented and analysed. Results: The most common antimicrobials prescribed were 3rd generation Cephalosporins namely Ceftriaxone, followed by Aminoglycosides (Amikacin), Imipenams (Meropenam), Anti-Influenza Antiviral (Oseltamivir) and Oxazolidinones (Linezolid). A common trend of antibiotic overuse emerged due to paucity of resources to support decision making and choice of antibiotic. This led to patients being exposed to a high number of antibiotics with an associated increase in morbidity. Conclusions: Antibiotic resistance would remain a challenge until systems for rapid, precise and low cost detection of the causative micro-organisms and antibiotic sensitivity are developed, surveillance systems are increased and antibiotic stewardship programs are enforced.